1999
DOI: 10.1002/(sici)1521-4141(199912)29:12<4030::aid-immu4030>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

A ubiquitin-like protein which is synergistically inducible by interferon-γ and tumor necrosis factor-α

Abstract: A means of regulating the fate of intracellular proteins is their covalent conjugation to ubiquitin‐like proteins. A recently discovered ubiquitin‐like protein is called “diubiquitin” because it consists of two ubiquitin‐like domains in head‐to‐tail arrangement. Human diubiquitin is encoded at the telomeric end of the MHC class I locus and was previously found to be expressed in dendritic cells and mature B cells. We have extended the expression analysis of diubiquitin by reverse transcriptase‐PCR and Northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 13 publications
5
98
0
Order By: Relevance
“…MZF-1) responsiveness. The existence of these responsive sites is consistent with the observations that the expression of FAT10 can be induced by IFN-g, TNF-a and/or retinoids (Raasi et al, 1999;Dokmanovic et al, 2002).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…MZF-1) responsiveness. The existence of these responsive sites is consistent with the observations that the expression of FAT10 can be induced by IFN-g, TNF-a and/or retinoids (Raasi et al, 1999;Dokmanovic et al, 2002).…”
Section: Resultssupporting
confidence: 89%
“…FAT10 gene is localized to the telomeric end of the cluster of human major histocompatibility complex (MHC) class I (Fan et al, 1996) genes. In addition, it is expressed in dendritic cells and mature B cells (Bates et al, 1997) and can be synergistically induced by the IFNg and TNF-a cytokines (Raasi et al, 1999). Although the FAT10 gene resides at the telomeric end of the MHC class I genes, it was reported not to be a member of this class of genes Kumanovics et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand FAT10 may act as a regulator of NF-B signaling and on the other hand FAT10 expression itself is regulated by NF-B. As already pointed out, FAT10 mRNA and protein expression is highly and synergistically inducible in all cell types by the pro-inflammatory cytokines IFN-␥ and TNF-␣ (Aichem et al, 2010;Raasi et al, 1999;Ren et al, 2011) or by a combination of TNF-␣ and IL-6 as shown in HepG2 cells (Choi et al, 2014). In HCT116 cells it was shown, that TNF-␣ signaling via the TNF-␣ receptor 1 (TNFR1) induced FAT10 expression, a receptor mainly found on tumor and stromal cells where it mediates the activation of NF-B (Balkwill, 2009;Ren et al, 2011).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?mentioning
confidence: 95%
“…Ebstein and colleagues (Ebstein et al, 2012) showed that FAT10 could enhance the MHC class I presentation of the human cytomegalovirus (HCMV)-derived antigen pp65 in HeLa cells by about two-fold as compared to untagged pp65 and Schliehe and colleagues (Schliehe et al, 2012) showed that the degradation rate as well as the presentation of specific lymphocyte choriomeningitis virus (LCMV) epitopes on MHC class I molecules was enhanced when FAT10 was fused to the N-terminus of the LCMV nucleoprotein. Apart from its expression in mTECs FAT10 is also constitutively expressed in mature B cells and dendritic cells (Bates et al, 1997) and its expression is highly and synergistically inducible on mRNA and protein level in numerous tissues and cell types by the pro-inflammatory cytokines IFN␥ and TNF␣ (Aichem et al, 2010;Raasi et al, 1999). A recent publication showed, that a high induction of FAT10 expression is also achieved by a synergistic treatment of HepG2 cells with TNF-␣ in combination with IL-6 (Choi et al, 2014).…”
Section: Fat10 In Adaptive and Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation